Analysis of Entrepreneurial Orientation, Innovation, and Social Media on MSME Performance - Mutiara Shinta Kusmayadi; R. Deni Muhammad Danial; Resa Nurmala (Dinasti International Journal of Education Management And Social Science, 2025)
The study uses entrepreneurial orientation as variable X1, innovation as variable X2, social media as variable X3, and MSME performance as variable Y. The purpose is to determine the influence of entrepreneurial orientation, innovation, and social media on MSME performance through a quantitative approach with descriptive and associative methods. The research sample consisted of 114 convection MSME actors in Sukabumi City, selected using purposive sampling based on predetermined criteria. Multiple regression analysis is used as the statistical method in this research. The F test results show that entrepreneurial orientation, innovation, and social media simultaneously have a significant effect on MSME performance, where the F count is 225.106, which is greater than the F table value of 2.69. The T-test results reveal that entrepreneurial orientation positively and significantly affects MSME performance (2.344 > 1,658), innovation also has a significant positive effect (4.445 > 1,658), and social media shows a similar result (4.588 > 1,658). The coefficient of determination (R Square) is 0.860, indicating that 86% of MSME performance is influenced by the three independent variables, while 14% is explained by other factors not examined in this study. All variables fall within the very strong influence category.